An Analysis of Cultural Demention In Moana Movie : A Semiotics Study - Tarigan, Enina Putri Aurora Br; Manik, Sondang; Pasaribu, Arsen Nahum (HUMAN: South Asian Journal of Social Studies, 2024)
Abstract. Semiotics is the study of signs and symbols, and the way these signs and symbols are used to convey meaning, in semiotics signs can be words, images, sounds, or objects that have certain meanings in certain contexts. This research aims to analyze the semiotic meaning in the Disney movie Moana (2016) using Barthes' theory. The research focuses on the elements, visual and verbal in the film to reveal the denotative, connotative, and myth meanings contained in it. This research method uses descriptive qualitative, with data in the form of the movie Moana containing many meanings through visual and verbal signs. This research explores how the film's signs, symbols, and representations convey deeper meanings related to identity, culture, empowerment, and the relationship between humans and nature. Through visual and narrative elements, the film reflects the importance of Polynesian traditions, ocean symbolism, and the relationship between humans and the environment. In connotation, Moana can symbolize innocence, curiosity, and exploration, symbolizing the freedom of adventure and the infinity of nature. After the denotation and connotation meanings are revealed, a myth is formed in which Moana facing the ocean can illustrate the challenges and possibilities faced in life's journey, as well as the importance of courage to explore the world. The film conveys deeper meanings about tradition, identity, and humanity's relationship with nature through various symbols, signs, and rich cultural references. Keywords: Semiotics, Denotative, Connotative, Myth, Moana movie